The expression -22x + 3y = 6 in the form ax + by + c = 0 is -2x + 3y - 6 = 0
<h3>Linear Equations</h3>
The given equation is:
-2x + 3y = 6
Comparing the equation above with ax + by + c = 0
Rewrite -2x + 3y = 6 in the form ax + by + c = 0
-2x + 3y - 6 = 0
If -2x + 3y - 6 = 0 is compared with ax + by + c = 0
a = -2, b = 3, c = -6
Therefore, the expression-22x + 3y = 6 in the form ax + by + c = 0 is -2x + 3y - 6 = 0
Learn more on linear equations here: brainly.com/question/14323743
Answer:
Step-by-step explanation:
fu**k my di*k
Answer:
X=-1/4
Step-by-step explanation:
<h2>8x=㏒₂/₅⁽²⁵/⁴⁾</h2>